Pengaruh Beban Kerja Terhadap Turnover Intention dengan Dukungan Sosial Sebagai Variabel Pemoderasi pada Pekerja Milenial - Gustine Firdaus Lestari; Rasistia Wisandianing Primadineska (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
Abstract The purpose of this study was to test the effect of workload on turnover intention with social support as a moderator for millennial workers. This type of research is a quantitative research. The data in this study are primary data in the form of a questionnaire that has been distributed to 100 millennial workers. The sampling method used was purposive sampling technique. The data analysis technique used instrument test, basic assumption test, classic assumption test, and moderated regression analysis with the help of SPSS for windows version 22. The results of the workload study have a positive and significant effect on turnover intention of millennial workers. Social support is able to moderate by weakening the effect of workload on turnover intention of millennial workers.